Comparative investigation of the detective quantum efficiency of direct and indirect conversion detector technologies in dedicated breast CT - Kuttig, Jan; Steiding, Christian; Kolditz, Daniel; Hupfer, Martin; Karolczak, Marek; Kalender, Willi Alfred (Physica Medica, 2015)
To investigate the dose saving potential of direct-converting CdTe photon-counting detector technology for dedicated breast CT.We analyzed the modulation transfer function (MTF), the noise power spectrum (NPS) and the detective quantum efficiency (DQE) of two detector technologies, suitable for breast CT (BCT): a flat-panel energy-integrating detector with a 70 ?m and a 208 ?m thick gadolinium oxysulfide (GOS) and a 150 ?m thick cesium iodide (CsI) scintillator and a photon-counting detector with a 1000 ?m thick CdTe sensor.The measurements for GOS scintillator thicknesses of 70 ?m and 208 ?m delivered 10% pre-sampled MTF values of 6.6 mm(-1) and 3.2 mm(-1), and DQE(0) values of 23% and 61%. The 10% pre-sampled MTF value for the 150 ?m thick CsI scintillator 6.9 mm(-1), and the DQE(0) value was 49%. The CdTe sensor reached a 10% pre-sampled MTF value of 8.5 mm(-1) and a DQE(0) value of 85%.The photon-counting CdTe detector technology allows for significant dose reduction compared to the energy-integrating scintillation detector technology used in BCT today. Our comparative evaluation indicates that a high potential dose saving may be possible for BCT by using CdTe detectors, without loss of spatial resolution.
EVALuna2:10106

High Atomic Number Contrast Media Offer Potential for Radiation Dose Reduction in Contrast-Enhanced Computed Tomography - Rößler, Ann-Christin; Hupfer, Martin; Kolditz, Daniel; Jost, Gregor; Pietsch, Hubertus; Kalender, Willi Alfred (Investigative Radiology, 2015)
Spectral optimization of x-ray computed tomography (CT) has led to substantial radiation dose reduction in contrast-enhanced CT studies using standard iodinated contrast media. The purpose of this study was to analyze the potential for further dose reduction using high-atomic-number elements such as hafnium and tungsten. As in previous studies, spectra were determined for which the patient dose necessary to provide a given contrast-to-noise ratio (CNR) is minimized.We used 2 different quasi-anthropomorphic phantoms representing the liver cross-section of a normal adult and an obese adult patient with the lateral widths of 360 and 460 mm and anterior-posterior heights of 200 and 300 mm, respectively. We simulated and measured on 2 different scanners with x-ray spectra from 80 to 140 kV and from 70 to 150 kV, respectively. We determined the contrast for iodine-, hafnium-, and tungsten-based contrast media, the noise, and 3-dimensional dose distributions at all available tube voltages by measurements and by simulations. The dose-weighted CNR was determined as optimization parameter.Simulations and measurements were in good agreement regarding their dependence on energy for all parameters investigated. Hafnium provided the best performance for normal and for obese patient phantoms, indicating a dose reduction potential of 30% for normal and 50% for obese patients at 120 kV compared with iodine; this advantage increased further with higher kV values. Dose-weighted CNR values for tungsten were always slightly below the hafnium results. Iodine proved to be the superior choice at voltage values of 80 kV and below.Hafnium and tungsten both seem to be candidates for contrast-medium-enhanced CT of normal and obese adult patients with strongly reduced radiation dose at unimpaired image quality. Computed tomography examinations of obese patients will decrease in dose for higher kV values.
EVALuna2:10116